Non-invasive Tear Film Assessment in Normal Population: Effect of Age, Sex, and Interparametric Relationship - Singh, Swati; Srivastav, Saumya; Mohamed, Ashik; Basu, Sayan (Frontiers in Medicine, 2022)
Purpose: To investigate age- and sex-related differences in tear film parameters of normal Indian population and study interparametric relationships. Methods: Healthy subjects with no ocular disease (median ocular surface disease index=0) were subjected to an automated evaluation of tear meniscus height (TMH), non-invasive tear breakup time (NIBUT) using Keratograph 5M (OCULUS GmbH, Wetzlar, Germany), and tear osmolarity using the TearLab Osmolarity System (TearLab Corporation, California, USA). A mixed-effects model with random intercepts at the patient level was used to evaluate the relationships between explanatory (age, gender, and tear osmolarity) and outcome variables (TMH and NIBUT). Results: A total of 237 subjects (474 eyes; 150 males) were enrolled with a mean age of 40 ± 17 years (range, 10 to 78 years). The mean values (± standard deviation) of TMH, NIBUT, and tear osmolarity were 0.34 ± 0.07 mm, 10.95 ± 2.02 s and 289.0 ± 5.8 mOsm/L, respectively. Age had a significant positive relationship with TMH (p<0.0001; 0.002 mm/year; r=0.12), but there was no effect on NIBUT (p = 0.26) and tear osmolarity (p = 0.27). There were no sex-based differences in tear film parameters. Interparametric relationship revealed no significant association between TMH and NIBUT (p = 0.12) or tear osmolarity and TMH (p = 0.83) or tear osmolarity and NIBUT values (p = 0.48). Conclusions: In a normal Indian population, TMH is weakly affected by age and is independent of sex, NIBUT, and tear osmolarity. Tear breakup time and osmolarity show no significant age- and sex-related variation.